FAKTOR RISIKO KURANG ENERGI KRONIS PADA IBU HAMIL DI JAWA BARAT (Analisis Lanjutan) - Iman Sumarno (Persagi, 2005)
ABSTRACTBackground: Cronict Energy Deficit (CED) in pregnancy reduce the quality of human resources. It is a high risk of low birth weight babies and a high risk of maternal mortality and sickness. Therefore,it is a priority to solve the problem. In 2002 the Province of West Java conducted mapping of CED in pregnant women. Objective: This article is an advance analysis of the risk factor of the CED past the analysis of the report to the local government of West Java. Method: The design is a rapid survey that is planned to represent each districts in the Province of West Java. Within each district is drawn systematically 30 clusters. Using maximum varience of variance of 50% the sample of each district is 420 pregnant women. The main data are hemoglobin concentration,Upper arm circumference, socioeconomic of the household sample, and history of health and pregnancy. Results: It found that the education level of the pregnant women is vary from never had schools to the university, and mostly 42,3% are graduated from middle school. Average expenditure for food over total expenditure is 71,8%. The prevalence of CED is 30,6% in the Province of West Java, the lowest is 19,3% in the city of Bandung and the highest is 50,7% in the district of Purwakarta. The risk factors of CED are as follows: Ever has sick, percent food expenditure, anemic and wasting before pregnancy are high risk of CED. Using contaceptics devices before pregnancy, graduated from high school, and ever had miscarriage are protective for CED. The most high risk is wasting before pregnancy with the risk of 2.562 and the most protective is using contraceptive device with risk of 0,565 times. Conclusion: Based on the above analysis of the effort to overcome the CED in pregnancy should be a preventive before pregnant or even before marriage. [Penel Gizi Makan 2005,28(2): 66-73] Keywords: chronic energy, pregnant women, risk factors